Per capita Carbon Dioxide emission in the developing economies: Ccnvergence or divergence? / Siti Ayu Jalil - Jalil, Siti Ayu (Faculty, 2016)
This study analyzes the convergence of per capita carbon dioxide emission for 126 developing countries situated in Africa, Latin America and the Caribbean, Middle East and North Africa, as well as Asia and the Pacific regions from 1971 to 2009. It employs the current technique proposed by Phillips and Sul (2007) also known as the log-t test. This method is crucial due to its ability to determine the possibility of club convergence that may arise if result shows a divergent pattern. The analysis is significant in order to propose climate change proposals besides being an incentive for developing countries to participate seriously in controlling their emission level. Empirical evidence shows the developing countries portray a convergent pattern of per capita carbon dioxide emissions.